Pedagogi Positif dalam Pendidikan Jasmani (Literature Review) - Rizky, Muhammad Yanuar; Mutohir, Toho Cholik; Suroto, Suroto (Jurnal Porkes, 2022)
This study aims to reveal the role of positive pedagogy in physical education during the COVID-19 pandemic.This study aims to provide a comprehensive synthesisinformatio of relevant studies voncerningabout the role of positive pedagogy in physical education during the covid 19 pandemic. This study uses a literature review method by  adopting the Preferred Items for Systematic Reviews and Meta Analyses: PRISMA as a using comprehensive strategy focusing relevant such as  such as articles in the research database. The databases used are Pubmed / MEDLINE, Scopus, Web of Science, and Embase. The keywords used in the search were pedagogy, motor skills, sports, positive pedagogy, and children. There were 20 articles obtained, and 5 selected articles were analyzed through the objectives, topics, sample size, research protocol, and results of each article. The results of this study explain that positive pedagogy that includes a holistic perspective can produce fun learning and the formation of movement competencies and students become better The results of this study explain that positive pedagogy increases motivation, directs development, forms self-efficacy, increases social responsibility, suppresses bullying behavior, and can improve psychomotor and cognitive aspects. It is hoped that teachers can apply positive pedagogy that includes a holistic perspective so that it can produce fun learning and the formation of movement competence and knowledge of students for the better.